Cover Image, Volume 171B, Number 4, June 2016. Issue 4 (June 2016) - Guffanti, Guia; Gaudi, Simona; Klengel, Torsten; Fallon, James H.; Mangalam, Harry; Madduri, Ravi; Rodriguez, Alex; DeCrescenzo, Paula; Glovienka, Emily; Sobell, Janet; Klengel, Claudia; Pato, Michele; et al.
Abstract : The cover image, by Fabio Macciardi et al., is based on the Research Article LINE1 insertions as a genomic risk factor for schizophrenia: Preliminary evidence from an affected family, DOI:10.1002/ajmg.b.32437 .